SISTEM PANASBUMI BERDASARKAN ANALISIS GEOKIMIA AIR PANAS DAERAH AMOHOLA DAN SUMBERSARI, KECAMATAN MORAMO, KABUPATEN KONAWE SELATAN, PROVINSI SULAWESI TENGGARA - Aprilia, Fitriani Dewi; Yuningsih, Euis Tintin; Patonah, Aton; Rezky, Yuano; Yushantarti, Anna; Nurdin, Asep (Bulletin of Scientific Contribution, 2015)
The research area is located in Amohola and Sumbersari, Moramo sub-district, Konawe South regency, Southeast Sulawesi Province. Geographically located between 122°35’6,07" – 122°45'58,94" BT dan 4°5'20,28" – 4°16'10,85" LS. The research areas have a stratigraphy consisted of Meta-limestones, Phylite, Schist, Quartzite, Conglomerates, Limestones, Carbonate Sandstone, Claystone, and sediment surface. Hot waters have temperatures ranging from 37,5oC to 50oC. The fluid geochemical data affirm that the Amohola area has Chloride type of water, which indicates it is close to the heat source, whereas in Sumbersari area has Bicarbonate water type, which indicates that the fluid has affected by meteoric water. Geothermal system in these two areas assumed that has separated by tectonic activity and the emersion of the lithology affected the chemical content of the hot fluid. The Geotermometer indicates that the subsurface of Amohola manifestations temperatures are around 146°C (medium enthalpy), whereas in Sumbersari 43°C (low enthalpy).